Carbon Nanodots: Assigning Electronic States in Carbon Nanodots (Adv. Funct. Mater. 44/2016). (November 2016) - Strauss, Volker; Kahnt, Axel; Zolnhofer, Eva M.; Meyer, Karsten; Maid, Harald; Placht, Christian; Bauer, Walter; Nacken, Thomas J.; Peukert, Wolfgang; Etschel, Sebastian H.; Halik, Marcus; Guldi, Dirk M.
Abstract : Pressure synthesized carbon nanodots are investigated by the multidisciplinary team of D. M. Guldi and co‐workers on page 7975. The cover illustrates the reductive or oxidative charging of the carbon nanodots (pCNDs) at electrode surfaces. The relation between the dot's surface states and their optical features is revealed to be fairly complex. Future work should address the transformation of functional groups upon oxidation or reduction.